Concepts in Plant Metabolomics - Nikolau, B.J; Wurtele, Eve Syrkin (Springer Netherlands : Imprint: Springer, 2007)
Analogous to genomics, which defines all genes in a genome irrespective of their functionality, metabolomics seeks to profile "all" metabolites in a biological sample irrespective of the chemical and physical properties of these molecules. Metabolomics has the potential of defining cellular processes as it provides a measure of the ultimate phenotype of an organism, as defined by the collage of small molecules, whose levels of accumulation is altered in response to genetic and environmentally induced changes in gene expression. This book presents a guide for new practitioners of metabolomics, providing insights as to the current use and applications of metabolomics.